Self-discontinuity in behavioral addictions: A psychodynamic framework - Gianluca Santoro; Alessandro Musetti; Antonino Costanzo; Adriano Schimmenti (Addictive Behaviors Reports)
Models based on substance use criteria have been employed to classify maladaptive engagement in various everyday activities as genuine addictions. However, symptom-based models have potential limitations, which includes in some cases reduced clinical utility and an increased risk of diagnostic inflation. The current article presents an alternative psychodynamic theoretical framework to elucidate the psychological processes underlying the development of putative behavioral addictions. According to this framework, behavioral addictions are conceptualized as strategies for regulating overwhelming feelings rooted in childhood trauma. Exposure to childhood trauma may lead to the segregation of unbearable trauma-related mental states from awareness through persistent dissociative processes. Thus, behavioral addictions may provide individuals with an illusory sense of control over unbearable feelings while simultaneously reinforcing the segregation of trauma-related mental states. The compulsive engagement in such activities can be seen as an attempt at self-medication, though it ultimately exacerbates discontinuities in self-experience. This theoretical framework is further illustrated through a clinical vignette, highlighting its implications for both assessment and treatment.